Integration of Dissolved Analysis and Total Quality Management to reduce costs and improve product quality - سرور منال جبار; عبد الرضا دعاء احمد (Journal of Economics and Administrative Sciences, 2018)
there is a need to use the teardown Technique in a various fields and different motives and used often by economic units as a technique to help other techniques for example, used by some economic units for the analysis of other economic units of products in order to work on the development of products and look for opportunities to improve product quality and avoid product errors competitor or reduce its costs, in addition to the services provided by quality control is used ISO 17025 integration with unassembled analysis to adjust the quality of the product by comparing the pieces produced with designed models that are also the product as a whole compared with the original design To ensure the integrity of the schemas and documents, which means that the analysis is focused on the dismantling of access to a product of high quality. In this research will be unassembled technique possible analysis technique intake to achieve reduced costs and improved quality through integration with the overall quality management tools due to the importance of comprehensive quality management ensure that products satisfy customers and beneficiaries because the economic units and the various put customer satisfaction at the top of the pyramid of priorities. When check Customer satisfaction about product quality and price The company’s business continues and continues to be produced. And it will present this research background theory tirelessly unassembled and total quality management and tools of analysis technology, will also be a framework proposal for a statement integration role between the analytical technique unassembled with total quality management tools in order to improve product quality and reduce its cost, considering the possible framework that provides a solution to the problem Which is characterized by low product quality and high costs.